THE EFFECT OF KATUK LEAF (Sauropus androgynus L. Merr) EXTRACT ON DRINKING WATER ON PHYSICAL QUALITY OF EGG IN LOHMANN BROWN LAYING UP TO 22-30 WEEKS OF AGE - A. R., Vicky; Siti, N. W.; Bidura, I G. N. G. (Jurnal Peternakan Tropika; Vol 6 No 2 (2018): May - August 2018, 2018)
Eggs is one of the ingredients of animal origin that is of high nutritional value because it contains substances that are needed by the human body such as protein, fat, vitamins, minerals, and has a high digestibility.  Egg quality is a term that connects standards to a variety of eggs. Egg quality determination and measurement includes two things are exterior and interior quality.  One effort made in improving the quality of chicken eggs can be done by adding katuk leaf water extract through drinking water. This research to determine the effect of katuk leaf water extract ( Sauropus androgynus L. Merr) through drinking water on the physical quality of chicken eggs Lohmann Brown aged 22-30 weeks for 12 weeks in Dajan Peken Village, Tabanan, Bali.  The design used in this research was Completely Randomized Design with three treatments and six replications.  The treatments is chickens fed ration without addition of katuk leaf water extract in drinking water as control (K0), rationed chicken with addition of 3% katuk leaf water extract in drinking water (K1), and chicken fed with ration katuk leaf water extract 6% in drinking water (K2). The variables observed is egg weight, percentage of egg whites,percentage of egg yolk, percentage of eggshell and egg shell thickness.  The results showed that on treatment of K1 and K2 significantly (P <0.05) increased egg weight, percentage of egg yolk, percentage of egg shelland egg shell thickness, compared with K0.  But the percentage of white egg decrease compared to chicken that is not given katuk leaf water extract (K0).  Based on the results of this research can be concluded that the provision of katuk leaf water extract ( Sauropus androgynus L. Merr) 3% and 6% through drinking water can increase egg weight, percentage of egg yolk, percentage of egg shell, eggshell thickness and a decrease in the percentage of egg white Lohmann Brown chicken aged 22-30 weeks. Keywords: egg, Lohmann Brown, katuk leaf water extract, physical quality